Standardization of Records in Orthodontics. Part 1: Static Photographs - Faruk İzzet Uçar; Tancan Uysal; Ali Osman Bengi (Galenos Yayinevi, 2010)
Because of the greater usage of the photographic records in orthodontic clinics; in the present review, taking photographic records, standardization, problems, solutions and some practical information will be mentioned.